ANIMASI GAMELAN BERBASIS FREKUENSI SUARA - Yoga Prisma Yuda; M Suyanto; Sukoco - (MULTITEK INDONESIA, 2018)
"Gamelan Animation Based Base On Sound Frequency" is a study aimed to find out how to make 3D gamelan animation automatically in accordance with the input of gamelan sound. The gamelan instrument used in this research is the type of saron instrument. The number of blades used in this study 7 pieces, according to the number of saron blades. The final result of this research is 3D animation of saron gamelan. Software used in this research is Blender 3D. This research requires several processes such as in sound frequency analysis, each saron gamelan blade has a slightly different frequency value. In the object hammer required armature or rigging that serves to move the hammer. Each armature is supplied by the driver as a link between the armature and the sound frequency graph. The object of the saron hammer, can move based on the frequency graph. The results showed that with the input frequency of saron the object of animation can move according to the time of the sound of the gamelan saron.